Technology-Based Business Idea Blueprint Bling Tracker / Muhammad Nur Aidil Ariff Muhamad Yusuf - Muhamad Yusuf, Muhammad Nur Aidil Ariff (2020)
SurgeKey is a business company that focusing on the production of key chain that bring benefit and easy the user. SurgeKey is based at Seberang Jaya, Penang. This business has invented a new product named Bling Tracker for the society in fulfilling their demand and solve their problems in finding their lost belongings. Bling Tracker is developed for the consumers to be installed at their belongings such as keys. Besides that, the app can be found on Play Store for Android and App Store for IOS. Bluetooth are required to connect the app and tracker. When the consumer activate the app, the tracker will produce a loud sound so the consumer can find the keys faster. Hence, I am using an attractive key chain to attract people for buying it and make their keys more beautiful. So besides the consumer can find the keys easier, it makes their keys look great